Projeções cartográficas: uma experiência no livro aberto de matemática e na formação continuada de professores - Zanon, Lucas Schimith (2022)
In 2018, the National Curricular Common Base (NCCB) was released, which aims to determine the skills (general and specific), habilities and essential learning that must be developed during each stage of basic education. In this document, among the changes that occurred, a skill regarding understanding Cartographic Projections in the Mathematics subject to be studied in High School was added. Thinking about how the NCCB skills can be worked in the classroom, a group of teachers, including the author of this dissertation, has been writing a didactic material, called Livro Aberto de Matemática (LAM), in which the topic Cartographic Projections is approached, as recommended by the NCCB. Thus, this dissertation aims to investigate the knowledge of mathematics teachers (and undergraduates) about Cartographic Projections. To achieve this goal, we designed and implemented a workshop held remotely, which had synchronous and asynchronous activities. During the workshop, we presented the chapter created on Cartographic Projections, discussed some activities with the participants and used four questionnaires and the recordings of the synchronous meetings as an instrument for data collection. Through a qualitative analysis of the answers given in the first questionnaire available, most participants reported not feeling confident to teach Cartographic Projections.